THE EFFECT OF PICTORIAL RIDDLES METHOD ON THE STUDENT'S ABILITY IN PARAGRAPH WRITING OF ENGLISH STUDY PROGRAM OF UNIVERSITY OF HKBP NOMMENSEN PEMATANGSIANTAR - Sinaga, Asima Rohana Sinaga; Silalahi, Dumaris Elseria; Marpaung, Tiarma Intan; Simanjuntak, Ramindo Rini Sari (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2020)
This research aims to see the effect The Pictorial Riddles Method on student writing ability to write descriptive paragraphs in the first semester students at HKBP Nommensen University of Pematangsiantar. In each course: Paragraph Writing, many students can not start writing descriptive sentences where most do not know how to start them due to lack of vocabulary and difficulty in organizing ideas into effective paragraph structures. Therefore, this experimental research was conducted to determine the effect of The Pictorial Riddles Method on students' writing abilities. This study uses a quasi-experimental method using pre-test and post-test in the experimental and control groups, with a quantitative research design. The research sample taken was 2 classes consisting of 60 students, where PI. A2 consist of 30 students as an experimental class, and PI. A1 consist of 30 students as a control class. The results of this study found that the mean post-test of the experimental group was 78.2 and the mean of the control class was 61.3. This study also found that the t-test result was higher than the t-table, which was 3.2>1.67 at df: 60 and the significance level was 0.05. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (ha) was accepted. So it can be concluded that the Pictorial Riddle Method has an effect on the ability to write descriptive texts for students in the first semester at HKBP Nommnsensen University of Pematangsiantar.